Dolerite Fines Used as a Calcium Source for Microbially Induced Calcite Precipitation Reduce the Environmental Carbon Cost in Sandy Soil - Carla C. Casas; Alexander Graf; Nicolas Brüggemann; Carl J. Schaschke; M. Ehsan Jorat (Frontiers in Microbiology, 2020)
Microbial-Induced Calcite Precipitation (MICP) stimulates soil microbiota to induce a cementation of the soil matrix. Urea, calcium and simple carbon nutrients are supplied to produce carbonates via urea hydrolysis and induce the precipitation of the mineral calcite. Calcium chloride (CaCl2) is typically used as a source for calcium, but basic silicate rocks and other materials have been investigated as alternatives. Weathering of calcium-rich silicate rocks (e.g., basalt and dolerite) releases calcium, magnesium and iron; this process is associated with sequestration of atmospheric CO2 and formation of pedogenic carbonates. We investigated atmospheric carbon fluxes of a MICP treated sandy soil using CaCl2 and dolerite fines applied on the soil surface as sources for calcium. Soil-atmosphere carbon fluxes were monitored over 2 months and determined with an infrared gas analyser connected to a soil chamber. Soil inorganic carbon content and isotopic composition were determined with isotope-ratio mass spectrometry. In addition, soil-atmosphere CO2 fluxes during chemical weathering of dolerite fines were investigated in incubation experiments with gas chromatography. Larger CO2 emissions resulted from the application of dolerite fines (116 g CO2-C m–2) compared to CaCl2 (79 g CO2-C m–2) but larger inorganic carbon precipitation also occurred (172.8 and 76.9 g C m–2, respectively). Normalising to the emitted carbon to precipitated carbon, the environmental carbon cost was reduced with dolerite fines (0.67) compared to the traditional MICP treatment (1.01). The carbon isotopic signature indicated pedogenic carbonates (δ13Cav = −8.2 ± 5.0‰) formed when dolerite was applied and carbon originating from urea (δ13Cav = −46.4 ± 1.0‰) precipitated when CaCl2 was used. Dolerite fines had a large but short-lived (<2 d) carbon sequestration potential, and results indicated peak CO2 emissions during MICP could be balanced optimising the application of dolerite fines.